Human bocavirus in fecal samples of neonates hospitalized in Belém, Pará (Research, Society and Development, 2023)
Gastroenteritis is among the leading causes of death in children under five worldwide. Rotavirus, calicivirus, enteric adenovirus and astrovirus are among the main viral etiological agents involved, however, in approximately 40% of cases, the causative agent is unknown. Recent studies have reported human bocavirus (HBoV) as a possible cause of acute gastroenteritis. This study aimed to investigate the HBoV genotypes in fecal samples of newborns hospitalized in Belém do Pará in 2011. This is a cross-sectional, retrospective, descriptive study, in which data were analyzed by real-time PCR. In 100 fecal samples from neonates (children aged 0 to 28 days), HBoV was detected in 20% of the samples, with higher detection rates in females. The highest peaks occurred in periods with lower rainfall records, with the HBoV1 genotype being the only one detected. Co-infection was identified between HBoV and rotavirus A in 10% of cases. The present study is a pioneer, as it reports the detection of this viral agent exclusively in neonates. Additional studies will be needed to elucidate the role of this virus in gastrointestinal infections in children aged less than 28 days.